2005
DOI: 10.4049/jimmunol.174.11.6809
|View full text |Cite
|
Sign up to set email alerts
|

Soluble MHC-Peptide Complexes Induce Rapid Death of CD8+ CTL

Abstract: Soluble MHC-peptide (pMHC) complexes, commonly referred to as tetramers, are widely used to enumerate and to isolate Ag-specific CD8(+) CTL. It has been noted that such complexes, as well as microsphere- or cell-associated pMHC molecules compromise the functional integrity of CTL, e.g., by inducing apoptosis of CTL, which limits their usefulness for T cell sorting or cloning. By testing well-defined soluble pMHC complexes containing linkers of different length and valence, we find that complexes comprising sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 51 publications
3
62
0
1
Order By: Relevance
“…Even if one discounts any CD8aa ligation-induced signalling or inhibition of signalling, the mere fact that some CD8ab + primary effector T cells express CD8aa is likely to aid their survival during the contraction phase, because CD8aa, or blocking of CD8ab, inhibits activation-induced cell death [11]. The finding that the expression of CD8aa is reversible and is absent on long term CD8 + memory cells allays the concern that selection of CD8aa + memory cells may compromise their sensitivity for recall responses.…”
mentioning
confidence: 99%
“…Even if one discounts any CD8aa ligation-induced signalling or inhibition of signalling, the mere fact that some CD8ab + primary effector T cells express CD8aa is likely to aid their survival during the contraction phase, because CD8aa, or blocking of CD8ab, inhibits activation-induced cell death [11]. The finding that the expression of CD8aa is reversible and is absent on long term CD8 + memory cells allays the concern that selection of CD8aa + memory cells may compromise their sensitivity for recall responses.…”
mentioning
confidence: 99%
“…8D). Although the PE fluorescence reached background within 20 -30 s, the Cy5 fluorescence reached background only after 300 -350 s. The Cy5 fluorescence decrease exhibited half-maximal dissociation in the range of 98 -118 s. Importantly, the monomer dissociation reached background levels, which is in contrast to dissociation experiments with BSP multimers, in which complete dissociation is typically not reached because of multimer rebinding and/or internalization (8,9). The experiments gave well reproducible results when performed in the cold; at elevated temperatures the monomer dissociation were too rapid to be reliably measured (data not shown).…”
Section: Pe-nta 2 -A2/peptide Multimers: a New Type Of T Cell-stainingmentioning
confidence: 54%
“…Because we have shown that the induced dissociation of DTB multimers from CTL is sufficiently rapid to prevent intracellular Ca 2ϩ mobilization (4), the same is expected for NTA-His tag multimers. Intracellular Ca 2ϩ mobilization is required for most CTL functions, including multimer-induced CD8ϩ T cell death (8,26,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, when a cell surface marker-specific antibody is injected to study the role of that molecule in EAE, the antibody might have a clinical effect on the disease, but it could be due to a multitude of mechanisms. The antibody could deplete the marker positive cells via the activation of complement, antibody-dependent cell-mediated cytotoxicity (ADCC) or apoptosis (Cebecauer et al, 2005), which in turn may be associated with a varying degree of inflammation causing unaccounted effects. Alternatively (or in addition) antibodies can inactivate or activate the marker positive cells, with variable bystander cell involvement.…”
Section: Experimental Autoimmune Encephalitis (Eae)mentioning
confidence: 99%